Estimator not a teacher (histogram) to estimate probability function - يوسف مناف (Journal of Economics and Administrative Sciences, 2009)
In this paper we introduce several estimators for Binwidth of histogram estimators’ .We use simulation technique to compare these estimators .In most cases, the results proved that the rule of thumb estimator is better than other estimators.